Peran Guru Pendidikan Agama Islam dalam Mengembangkan Karakter Kepedulian Sosial Siswa SMP di Yayasan Pendidikan Nurul Hasanah Tembung - Nissa Zahru Oktavianti (STIKes Ibnu Sina Ajibarang, 2024)
This article aims to describe the role of teachers in developing the social care character of junior high school students at the Nurul Hasanah Tembung Education Foundation. These findings emphasize the importance of the active role of teachers in forming socially caring character, which is expected to create a generation that is more sensitive to their social environment. The method used is a qualitative approach with in-depth interviews and observations of teachers and students. The research results show that teachers act as role models, motivators and facilitators in the process of developing social awareness. Through daily activities, extracurricular activities, and the integration of social values ​​in learning, teachers are able to encourage students to actively participate in social issues. Apart from that, support from the foundation and collaboration with parents also contributed to the success of this program.